Childhood stress - sources and manifestations - Jurin, Tanja (Array, 2009)
The aim of this study was to determine the sources of stress and its psychological and physical manifestations in school children. Namely, we were interested in determining whether the sources or manifestations of stress change with maturation, and to determine whether any gender differences existed. The study was conducted on a sample of 130 male and 139 female pupils, aged between 10 and 14, from a single elementary school in Zagreb. Sources of stress (estimates of levels of stress in specific areas of pupils’ life), physical manifestations of stress (a silhouette on which they indicated on which parts of the body they felt stress), and psychological manifestations of stress (depression, anxiety, self-respect) were assessed. Results revealed that school is the strongest source of stress for children of both genders. Apart from school, younger girls also reported relationships with their siblings as stressful. Older girls reported increasing problems in their relationships with friends and parents. Amongst fourteen year old girls, stress about their appearance becomes as strong and prominent as stress about school. Sources of stress among boys were relatively stable. In comparison to younger boys, older boys more frequently reported problems with their parents. Physical manifestations of stress in girls were located in different parts of the body, mostly in the head, neck, shoulders and chest. Interestingly, stress most commonly manifests through the arms and legs amongst boys. The overall intensity of a child’ s experienced stress was found to be associated with lower self-respect, higher anxiety and depression. The results of this study indicate gender and age differences in the sources and manifestations of stress throughout childhood. The results will be discussed within a framework of cognitive and evolutional models.